Pedagogía de alteridad para el fortalecimiento de procesos de inclusión de identidad autóctona en el aula - Riera Quito, Claudia Gabriela (2018)
The research with the topic Pedagogy of Alterity, for the strengthening of processes of the inclusion of indigenous identity en the classroom, it was carried out with the objective of demonstrating how the Pedagogy of Alterity strengthens the processes of inclusion of indigenous identity in the classroom, and is based on the pragmatism of John Dewey who states that for the learning process should be considered of prior knowledge of students, in the philosophical thinking of Josef Esternann, who analyzes the existence of Andean philosophy as the opening for the existence of interculturality and diversity. In the research, the qualitative approach is approached, starting from the assumption of the existing relationship between the two study variables: Pedagogy of Alterity and autochthonous identity en the classroom. The unit of analysis corresponds to 65 third-year General Unified Baccalaureate students of the “Amalia Gallegos Díaz Unit”. The method that rules the research is the deductive method, it starts with the assumption that the students of the Third Year of the Unified General Baccalaureate of the Amalia Gallegos Díaz Unit”, of the city of Riobamba at the end of the academic period 2017 – 2018 know the topics of inclusion of indigenous identity treated by the Pedagogy of Alterity. It is concluded that the Pedagogy of Alterity, through self-recognition, collaborative work and ethno mathematics, strengthens the processes of inclusion of autochthonous identify in the classroom. It is recommended to attend to the request made by the authorities of the educational unit and to socialize the results obtained in the research in order to contribute with the institutional improvement.